2019
DOI: 10.1093/ofid/ofz322
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Survey of Cytomegalovirus Prevention Strategies in Kidney Transplant Recipients in a Resource-Limited Setting

Abstract: Objective Strategies to prevent cytomegalovirus (CMV) infection in resource-limited settings have been under-explored. We investigated CMV prevention strategies utilized among transplant centers in Thailand. Method A questionnaire on CMV prevention strategies for kidney transplant (KT) recipients was developed using a web-based electronic survey website (www.surveymonkey.com). The survey was delivered to 31 transplant centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This large cohort study is limited by the lack of information on CMV preventive strategies in the SOT and HSCT cohorts. Regardless of the consensus guidelines for CMV prevention in transplant settings, standardized protocols, including dosage or duration of anti-CMV drugs, strategies or surveillance of prevention (especially, application of recent hybrid approaches), cut-off thresholds of CMV viral load, monitoring methods for preemptive therapy, or management of refractory/recurrent/relapsed cases would be quite heterogeneous for each institution or physician 30 , 35 , 45 , 60 . This is because sophisticated strategies are based on tailored management in accordance with several risk factors and clinical conditions 30 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…This large cohort study is limited by the lack of information on CMV preventive strategies in the SOT and HSCT cohorts. Regardless of the consensus guidelines for CMV prevention in transplant settings, standardized protocols, including dosage or duration of anti-CMV drugs, strategies or surveillance of prevention (especially, application of recent hybrid approaches), cut-off thresholds of CMV viral load, monitoring methods for preemptive therapy, or management of refractory/recurrent/relapsed cases would be quite heterogeneous for each institution or physician 30 , 35 , 45 , 60 . This is because sophisticated strategies are based on tailored management in accordance with several risk factors and clinical conditions 30 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, various strategies like preemptive therapy, antiviral prophylaxis, hybrid approaches (continuous surveillance after prophylaxis for CMV viremia with preemptive therapy), and CMV-specific immunity-guided approaches are being used for effective control of CMV infection in the LT alike in other SOT ( 6 , 7 ). However, antiviral prophylaxis and preemptive therapy are the most commonly used strategies in many centers.…”
Section: Introductionmentioning
confidence: 99%
“…Preemptive strategy on the other hand has been shown to decrease the incidence of late-onset CMV disease and increase in CMV-induced immune response ( 6 , 9 ). However, preemptive strategy essentially faces logistics challenges for medical centers and patient’s noncompliance with monitoring of CMV viremia ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent nationwide survey showed that almost 80% of Thai physicians implemented prevention strategies, including preemptive approaches (48%) and prophylaxis (45%). Prophylaxis is preferred for high-risk patients, such as those with a high level of immunosuppression (Bruminhent et al, 2019).…”
Section: Introductionmentioning
confidence: 99%